Family Function and Misuse of Drug in Adolescents in Indonesia - Oktriyanto, Oktriyanto; Amrullah, Hilma; Titisari, Anastasia Septya (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
In Indonesia drug in adolescents shows a number that tends to be high. This phenomenon is certainly an indication that there are character problems in children and adolescents in Indonesia, which certainly cannot be separated from the role of parents. In this case the function of parents and government support is needed in an effort to handle the use of drugs in teenagers in Indonesia. The results showed that the majority of adolescents who used drugs were more in adolescents who had heads of households with low education and had families with a low wealth index, were in whole families, and more in adolescents who lived in rural areas. Teenage boys tend to use drugs more than girls. Teenagers who use drugs have more characteristics of the 20-24 year age group,Ã‚Â low education and are not working. The factors that significantly affect the use of drug use among adolescents include socio-cultural functions, place of residence, adolescence, adolescent sex, work status, adolescent access to PIK-R programs, and knowledge of the impact of drugs.